(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article examines the formation of toponymy in the Kungrad district and the historical foundations of the changes observed there. The paper analyzes the laws of place name formation using the example of the toponym "Yelmurat Ahun Mosque" and nearby names such as Mashtaq Ata, Sorkól, and Jansyz, located in the area where Yelmurat Ahun—the teacher and maternal uncle of the classical Karakalpak poet Ajiniyaz Qosıbay ulı—lived. It is proven that the formation of toponyms is closely linked to the area’s relief, the people’s life experiences, and historical events. The significance of anthroponymic toponyms is also highlighted.